Correlation between Interleukin-6 and E-Selectin as a Marker of Endothelial Dysfunction in Rheumatoid Arthritis Patient without Traditional Cardiovascular Risk Factor - Jerry Eddya Putra Boer; Rudy Hidayat; Ika Prasetya Wijaya; Ikhwan Rinaldi (Indonesian Rheumatology Association, 2018)
Rheumatoid arthritis (RA) is an autoimmune disease which has recently been recognized to manifest as not only intraarticular but also extraarticular symptoms. Cardiovascular events, presented either subclinically or clinically, were discovered more in AR patients. Atherogenic inflammatory mediator in AR including interleukin-6 (IL-6) was thought to be one of nontraditional cardiovascular risk factor contributing to increase the endothelial dysfunction biomarker such as E-Selectin. This study was purposed to determine the correlation between inflammatory mediator and endothelial dysfunction event, especially between IL-6 and E-Selectin, in RA patient without traditional cardiovascular risk factor. A cross-sectional study was performed to 40 RA patients of Rheumatology Clinic of Cipto Mangunkusumo National General Hospital, Indonesia from September to November 2017. Measurement of the level of IL-6 and E-Selectin were performed using enzyme-linked immunosorbent assay (ELISA). Bivariate correlation analysis was performed to determine the correlation between those two biomarkers. The mean age of this study subjects was 44.9 (13.1) years and median of disease duration was 36 months. This study showed weak correlation between IL-6 and E-Selectin level, but not statistically significant.232, p=0.149). There is weak correlation between IL-6 and sE-Selectin in rheumatoid arthritis patient without traditional risk factor cardiovascular Keywords: traditional risk factor cardiovascular, E-Selectin, interleukin-6, pro inflammatory mediator, rheumatoid arthritis